Financing equitable access to antiretroviral treatment in South Africa - McIntyre Di; Cleary Susan (BMC Health Services Research, 2010)
Abstract Background While South Africa spends approximately 7.4% of GDP on healthcare, only 43% of these funds are spent in the public system, which is tasked with the provision of care to the majority of the population including a large proportion of those in need of antiretroviral treatment (ART). South Africa is currently debating the introduction of a National Health Insurance (NHI) system. Because such a universal health system could mean increased public healthcare funding and improved access to human resources, it could improve the sustainability of ART provision. This paper considers the minimum resources that would be required to achieve the proposed universal health system and contrasts these with the costs of scaled up access to ART between 2010 and 2020. Methods The costs of ART and universal coverage (UC) are assessed through multiplying unit costs, utilization and estimates of the population in need during each year of the planning cycle. Costs are from the provider’s perspective reflected in real 2007 prices. Results The annual costs of providing ART increase from US$1 billion in 2010 to US$3.6 billion in 2020. If increases in funding to public healthcare only keep pace with projected real GDP growth, then close to 30% of these resources would be required for ART by 2020. However, an increase in the public healthcare resource envelope from 3.2% to 5%-6% of GDP would be sufficient to finance both ART and other services under a universal system (if based on a largely public sector model) and the annual costs of ART would not exceed 15% of the universal health system budget. Conclusions Responding to the HIV-epidemic is one of the many challenges currently facing South Africa. Whether this response becomes a “resource for democracy” or whether it undermines social cohesiveness within poor communities and between rich and poor communities will be partially determined by the steps that are taken during the next ten years. While the introduction of a universal system will be complex, it could generate a health system responsive to the needs of all South Africans.